Lack of evidence for involvement of TonEBP and hyperosmotic stimulus in induction of autophagy in the nucleus pulposus - Liu, Chao (Sci Rep, 2017)
Nucleus pulposus (NP) cells reside in a physiologically hyperosmotic environment within the intervertebral disc. TonEBP/NFAT5 is an osmo-sensitive transcription factor that controls expression of genes critical for cell survival under hyperosmotic conditions. A recent report on NP and studies of other cell types have shown that hyperosmolarity triggers autophagy. However, little is known whether such autophagy induction occurs through TonEBP. The goal of this study was to investigate the role of TonEBP in hyperosmolarity-dependent autophagy in NP. Loss-of-function studies showed that autophagy in NP cells was not TonEBP-dependent; hyperosmolarity did not upregulate autophagy as previously reported. NP tissue of haploinsufficient TonEBP mice showed normal pattern of LC3 staining. NP cells did not increase LC3-II or LC3-positive puncta under hyperosmotic conditions. Bafilomycin-A1 treatment and tandem mCherry-EGFP-LC3B reporter transfection demonstrated that the autophagic flux was unaffected by hyperosmolarity. Even under serum-free conditions, NP cells did not induce autophagy with increasing osmolarity. Hyperosmolarity did not change the phosphorylation of ULK1 by mTOR and AMPK. An ex vivo disc organ culture study supported that extracellular hyperosmolarity plays no role in promoting autophagy in the NP. We conclude that hyperosmolarity does not play a role in autophagy induction in NP cells.